Electricity Anomaly Point Detection using Unsupervised Technique Based on Electricity Load Prediction Derived from Long Short-Term Memory - Salleh N.S.M.; Saripuddin M.; Suliman A.; Jorgensen B.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Anomaly detection; Brain; Errors; Forecasting; Gradient methods; Mean square error; Optimization; Statistics; Stochastic models; Stochastic systems; Anomaly detection; Electricity load; Electricity theft; Load predictions; Mean absolute error; Mean squared error; Optimizers; Point detection; Power providers; Unsupervised techniques; Long short-term memory